Знахідки нових видів риб у середній та верхній течії Південного Бугу - Мовчан, Ю.В.; Паньков, А.В.; Рабцевич, Ю.Є. (Вестник зоологии, 2002)
Сообщено о находках новых, ранее неизвестных для отдельных участков Южного Буга и в целом для его басссейна, видов рыб. Приведены краткие диагнозы этих рыб. Материал, собранный в коренном русле Южного Буга в пре-делах Хмельницкой и Винницкой областей, хранится в ихтиологических фондах зоомузея ННПМ НАНУ. Several species of fishes are recorded for the first time from certain locations in the Southern Bug and from its basin as a whole. Diagnoses are provided for all the species. The material was collected directly in the Southern Bug itself in Khmelnitsky and Vinnytsya districts. The Material is deposited in the collection of the Natural History Museum of the National Academy of Sciences of Ukraine.